DIGITAL INTEGRATED FINANCIAL CREDIT SCORING SEBAGAI PEMBAHARUAN HUKUM EKONOMI DI ERA DIGITAL SOCIETY 5.0 - Candya Upavata Kutey Karta Negara (Fakultas Hukum Universitas Udayana, 2023)
The purpose of this study is to determine the regulation and implementation of financial technology innovative credit scoring as a provider of digital credit scoring in Indonesian positive law, as well as the legal reconstruction of the application of Digital Integrated Financial Credit Scoring (DIFCS) as a catalyst for economic growth in the digital society. 5.0. This journal publishes doctrinal legal research that uses secondary data, a statutory approach, and a conceptual approach. (1) Financial technology innovative credit scoring arrangements have been controlled as part of one of the clusters in POJK 13/2018, according to the study findings in this research.To increase public access to the credit scoring system, the financial technology novel credit scoring concept uses the user's digital footprint, which is processed with artificial intelligence and machine learning. (2) Integrating the digital credit scoring system with the traditional banking credit scoring system into a digital integrated financial credit scoring (DIFCS) database may be a solution for increasing assessment accuracy and credit access for segments of society who do not have access to formal banking financial sector services.